How John works: storytelling in the fourth gospel - Estes, Douglas; Sheridan, Ruth (Resources for biblical study, 2016)
Cover -- Contents -- Abbreviations -- Introduction -- Genre -- Style -- Time -- Space -- Point of View -- Plot -- Characterization -- Protagonist -- Imagery -- Scripture -- Rhetoric -- Persuasion -- Closure -- Audience -- Culture -- Bibliography -- Contributors -- Ancient Sources Index -- Modern Authors Index -- Subject Index